Antigenic heterogeneity of a foot-and-mouth disease virus serotype in the field is mediated by very limited sequence variation at several antigenic sites. - Mateu, MG; Hernández, J; Martínez, M; Feigelstock, D; Lea, S; Pérez, J; Giralt, E; Stuart, D; Palma, E; Domingo, E (1994)
Antigenic variation in a major discontinuous site (site D) of foot-and-mouth disease virus (FMDV) of serotype C has been evaluated with neutralizing monoclonal antibodies. Isolates representing the major evolutionary sublines previously defined for serotype C were compared. Extensive variation, comparable to that of continuous epitopes within the hypervariable immunodominant site A (the VP1 G-H loop), was found. The amino acid sequences of the complete capsids of three antigenically highly divergent FMDVs (C1 Haute Loire-Fr/69, C5 Argentina/69, and C3 Argentina/85) have been determined and compared with the corresponding sequences previously determined for seven additional type C viruses. Differences in antigenicity are due to a very limited number of substitutions of surface amino acids accessible to antibodies and located within antigenic sites previously identified on FMDV. A significant number of residues at these positions were also replaced in monoclonal antibody escape mutants. Depending on the variants compared, replacements within site A or at site D, or at both sites, contributed significantly to their antigenic differences. Examples of divergence mediated by a few amino acid replacements were found among FMDVs of Europe and South America. The results suggest that within a serotype of FMDV, antigenically highly divergent viruses can arise in the field by very limited sequence variation at exposed key residues of each of several antigenic sites.